Transition Modelling for Axial Compressor Flows - Beevers, A. (Cranfield University, 2008)
Abstract The application of Menter's transition model (Menter et al. (2004a), here-after known as the ץ - θ model) available in the CFX CFD code, for use within an axial compressor design group was studied. Simulations of a range of turbomachinery applicable test cases were undertaken, including a range of transitional flat plates and a 2D compressor cascade. Results were com¬pared to experimental data and the results of simulations performed with standard turbulence models. The ץ - θ model significantly improved the prediction of the boundary layer development, compared to the turbulence models. Comparisons with ex¬perimental data were also good. Features such as mid-chord transitional separation bubbles were predicted with the ץ - θ model, but not with the turbulence models. The ץ - θ model offered no consistent improved accuracy over the κ - ω SST turbulence model when predicting leading edge separa¬tion bubbles. The more accurate simulation of the boundary layer enables a closer prediction of viscous losses. 2D and 3D unsteady simulations of a low-speed axial compressor stator blade boundary layer, subject to impinging rotor wakes, were conducted. The pur¬pose was to determine the performance of the ץ - θ model in this environment, as there is no available literature for this. For both simulations, the model gave a good qualitative agreement to experimental data in the prediction of passing rotor wake effects on the suction surface. The effects on the pressure surface transition region due to wake passing were poorly predicted. All models were simulated on low and high-speed axial compressor stages. Results showed no improvement over the turbulence models of the ץ - θ model to predict blade exit parameters. The ץ - θ model does not present a significant enough improvement in the prediction of the flow to warrant its regular use in the design of axial compressor blading. However, it presents a useful tool in the development of high lift compressor blading.